2011
DOI: 10.1111/j.1529-8817.2011.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

ENVIRONMENTAL CONTROL OF STALK LENGTH IN THE BLOOM‐FORMING, FRESHWATER BENTHIC DIATOM DIDYMOSPHENIA GEMINATA (BACILLARIOPHYCEAE)1

Abstract: Blooms of the freshwater stalked diatom Didymosphenia geminata (Lyngb.) M. Schmidt in A. Schmidt typically occur in oligotrophic, unshaded streams and rivers. Observations that proliferations comprise primarily stalk material composed of extracellular polymeric substances (EPS) led us to ask whether or not the production of excessive EPS is favored under nutrient-limited, high-light conditions. We conducted experiments in outdoor flumes colonized by D. geminata using water from the oligotrophic, D. geminata-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 45 publications
7
45
0
6
Order By: Relevance
“…Like many other HABs taxa, D. geminata exploits both inorganic and organic sources of P to support growth. This is supported by evidence from other studies; Kilroy and Bothwell (2011) showed that when a period of nutrient enrichment was followed by unenriched conditions, D. geminata division rates declined by 60% while mean stalk length increased by 250%. During low ambient supplies of inorganic P (i.e., phosphate), D. geminata cell division is P-limited Kilroy and Bothwell, 2011), and under such conditions, the upper parts of stalks stain strongly for organic P-scavenging phosphomonoesterase activity (Ellwood and Whitton, 2007;Aboal et al, 2012).…”
Section: B Factors Influencing Growthsupporting
confidence: 84%
“…Like many other HABs taxa, D. geminata exploits both inorganic and organic sources of P to support growth. This is supported by evidence from other studies; Kilroy and Bothwell (2011) showed that when a period of nutrient enrichment was followed by unenriched conditions, D. geminata division rates declined by 60% while mean stalk length increased by 250%. During low ambient supplies of inorganic P (i.e., phosphate), D. geminata cell division is P-limited Kilroy and Bothwell, 2011), and under such conditions, the upper parts of stalks stain strongly for organic P-scavenging phosphomonoesterase activity (Ellwood and Whitton, 2007;Aboal et al, 2012).…”
Section: B Factors Influencing Growthsupporting
confidence: 84%
“…Native means occurring before European settlement or before intercontinental travel and commerce became common and widespread. Documented cases of freshwater diatoms introduced from other continents since European settlement are not common (e.g., Edlund et al 2000, Spaulding et al 2010, Reid et al 2012, Kilroy and Bothwell 2011). If one accepts evolution and vicariance or “historical biogeography” as the prevailing mechanisms that explain diatom distributions (as opposed to unrestricted dispersal and “ecological biogeography”), then one must assume that all taxa are native, unless there is evidence to the contrary of their recent introduction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plankton drift net samples for eDNA, we collected water chemistry data that included total phosphorus, soluble reactive phosphorus (SRP), pH, nitrate, sulphate, chloride and specific conductance, which are thought to be predictive of D. geminata distribution or abundance (Kilroy & Bothwell, 2011;Bothwell et al, 2014;Bray et al, 2016). At Maryland sites, a 1 L grab sample of stream water was collected for laboratory chemical analyses at the Appalachian Laboratory (University of Maryland Center for Environmental Science), using standard protocols for each analyte (American Public Health Association (APHA), 2005).…”
Section: Field Samplingmentioning
confidence: 99%